Մանկահավաքն Օսմանյան կայսրությունում որպես աշխատուժի վերակազմակերպման միջոց - Շաքարյան, Արտակ («Զանգակ - 97»)
The shepherd who rose to become an illustriuos grand vezir was a figure that never ceased to fascinate European observers. However, in reality that picture was very seldom to occure: only very fews were getting posts at the central administration. Most of the boys levied by devshirme were lost at the battle-fields or uscd as labor force. Actually, the number of the levied boys was too large to be uscd by administration or even army.
Keywords: Պատմություն